Solusi Efektif Guru dalam Menerapkan Model Pembelajaran untuk Mengatasi Tantangan Pembelajaran Matematika di Sekolah - Sri Dahlia Lia; Imam Sujarwo (Advances In Education Journal, 2025)
Mathematics is an essential subject within the educational curriculum. However, students’ low interest in learning mathematics remains a major challenge. Mathematics learning requires greater attention and effort from teachers, students, and schools in order to create an engaging, interactive, and effective learning environment. This study was conducted to help mathematics teachers address these issues through the implementation of more appropriate and innovative learning models. The research employed a descriptive qualitative method by collecting data through observations of seventh-grade students’ test results at MTs Darul Aziz Manggis on the topic of one-variable linear inequalities, interviews with students and teachers, and documentation. The findings indicate that students’ low learning outcomes were caused by their inability to understand the context of the problems, leading them to solve questions based on logic rather than using the correct formulas. Low interest in mathematics also contributed to students being unfocused and passive. A feasible solution is the application of varied learning models that can help students better understand the material and increase their motivation to learn